Baião no vibrafone: ferramentas e possibilidades de adaptação - Mandelli, Byanca (2023)
In this research aspects concerning the practice of the popular genre baião applied to the vibraphone were addressed. This instrument is scarcely used in the context of Brazilian popular music, which results in a shortage of works and teaching materials for its application in this musical genre. To propose accompaniment lines for baião, an analysis of the primordial references of this genre was researched, having the zabumba as a base instrument. From that on, several adaptations and variations of the rhythmic figure of the zabumba to the vibraphone were proposed by using various specific instrumental techniques to carry out the adaptations. Still considering playing popular music on this instrument, a sequence of basic harmony studies was proposed, voice leading and chord inversion, which showed to be a great contribution to the study of popular music on vibraphone. Arrangements and etudes were prepared to target the application of the tools developed throughout the research.